The little psychotherapy book : object relations in practice - Frankland, Allan G. (Oxford University Press, 2010)
Aimed at beginning therapists and those new to object relations, this concise work introduces the reader to the practice of psychodynamic psychotherapy from an object relations (O-R) perspective in a dynamic and easy-to-follow way. One of the three main schools of psychodynamic psychotherapy, O-R is regarded as particularly challenging, both conceptually and practically. The book presents object relations in a clear and concise manner that makes it especially applicable for regular use in the clinical setting. Moreover, the author writes in a narrative style similar to actual psychotherapy sup.